As estratégias sociocognitivas nas crônicas de Rubem Braga - Queiroz, Creusa Maria Maia de (2015)
This work aims to show the text study development regarding its relationship with its sociocognitive context as well as to present socio-cognitive strategies, both for the analysis of eight chronicles written by Rubem Braga and published at Ai de Ti, Copacabana. Through the socio-cognitive approaches, both explicit, but also implicit that are present in Rubem Braga´s chronicles, we will able to lead the reader to the reflections on the issues surrounding the meaning of the text. From this assumption, the present study is justified by the need to deepen the knowledge and discussions on the problems faced on the notion of language as an interactive and dialogical activity, and should be understood as an active and constructive process in living people. Thus it should be noted that both what is on the surface of their narratives, but also all that lies beyond, contribute to the reader to perform their understanding of the text's meaning. The methodology is bibliographic and analytical and is divided in three stages. At first, all the textual language ways of the study process and the text of the theory will be shown. In the second part, the textual processing of reading and understanding of the text will be studied, and also the socio-cognitive strategies that contribute to the text sense. These studies will be conducted on the basis of textual linguistic study and socio-interactive researchers as Koch (1997, 2002, 2006, 2009), Koch and Elias (2012, 2013); Marcuschi (2008, 2012); Favero and Koch (2012); Bentes (2001); Fiorin (2006, 2013); Bentes (2004, 2006); Mendonça (2011); Arrigucci (1987, 2001). Thirdly, we will analyze eight chronicles by Rubem Braga, from his book entitled Ai de ti, Copacabana, chosen as the corpus of this research. Therefore, the aim of this work is to enable reflections that promote the understanding of proposed reading of Rubem Braga´s chronicles, so that new readers will come to source this matrix production and their speech of their day-to-day lives.